2018
DOI: 10.1111/jgh.14521
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of 732 ursodeoxycholic acid‐treated patients with primary biliary cholangitis: A single center follow‐up study from China

Abstract: Background and Aim The impact of male sex and past hepatitis B virus (HBV) infection on survival of primary biliary cholangitis (PBC) are issues at discussion. The aim of the present study was to identify risk factors for transplant‐free survival (TRS) in Chinese PBC patients who received ursodeoxycholic acid (UDCA), with special focus on the impact of male sex and past HBV infection. Methods We followed up PBC patients who received UDCA at our institute between January 2000 and December 2017 until their death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 23 publications
(62 reference statements)
3
26
1
Order By: Relevance
“…Among the 203 patients without complications who completed follow-up, 47.8% had cirrhosis at baseline, and the median follow-up time was 52 months (interquartile range: 28-75 months). The 5-year and 10-year TRS rates were 84.1% and 67.6%, respectively, which were consistent with the results of two other studies in China [19,20] but lower than those reported by the UK-PBC group [21]. By the end of follow-up, 121 patients (59.6%) had developed liver decompensation.…”
Section: Plos Onesupporting
confidence: 90%
See 1 more Smart Citation
“…Among the 203 patients without complications who completed follow-up, 47.8% had cirrhosis at baseline, and the median follow-up time was 52 months (interquartile range: 28-75 months). The 5-year and 10-year TRS rates were 84.1% and 67.6%, respectively, which were consistent with the results of two other studies in China [19,20] but lower than those reported by the UK-PBC group [21]. By the end of follow-up, 121 patients (59.6%) had developed liver decompensation.…”
Section: Plos Onesupporting
confidence: 90%
“…The reasons for the higher complication rates and lower survival rates in our cohort may be as follows: 1) the current cohort included a significant proportion of patients with advanced liver disease. The proportion of patients with compensated and decompensated cirrhosis was higher than that in a study conducted in Beijing [19] and that in a large cohort study conducted in Europe [22]. This may be because people in mainland China, especially those in less developed areas such as the northeast, do not have a high level of awareness of this disease.…”
Section: Plos Onecontrasting
confidence: 61%
“…9,25,26 The elevation of total bilirubin level associated with the adverse outcome of PBC patients has been confirmed by many other surveys. [9][10][11][27][28][29][30] The elevation of total bilirubin might reflect progression of PBC. 9 Therefore, there is no doubt that bilirubin is one of the risk factors of early biochemical nonresponse.…”
Section: Discussionmentioning
confidence: 99%
“…ALB, albumin; LLN, lower limit of normal; TBiL, total bilirubin; ULN; upper limit of normal study showed that men were more likely to have a shorter survival time than women in PBC patients treated with UDCA. 14 23 and Rotterdam criteria 9 ) but also an important predictor of the GLOBE score 6 and UK-PBC risk score. 10 Furthermore, Corpechot et al 5 reported that baseline TBiL levels were higher in patients with refractory disease.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, different biochemical response criteria were used to evaluate therapeutic efficacy in these studies. 6,[12][13][14] There are significant differences in the criteria for evaluating the UDCA response in PBC patients. 15 Given the potential risk of misidentification, the comprehensive evaluation of biochemical response can be superior to the use of a single criterion and could be helpful in risk stratification.…”
Section: Introductionmentioning
confidence: 99%